Analysis of Usability Using Heuristic Evaluation Method in The Raycare Hemodialisis Clinic Application - Yulfitri, Alivia; Indarwulan, Ayunda; Widayanti, Riya; Benny Chaniago, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Hemodialysis clinic application the raycare hemodialysis clinic medical record application is web-based and can be accessed by medical personnel namely doctors and nurses. Over the past 9 months there have been 4 changes of nurses that have led to the emergence of new nurses which takes about 2 months for features in the application. This time is considered to be less than optimal because the application of patient medical records is important and important in the company's business processes. This research was conducted with a heuristic evaluation method to find the use of problems in interface design. There are ten heuristic aspects that are used, namely: visibility of system status, match between system and the real world, user control and freedom, standards and consistency, help and user recognize, diagnose and recover from errors, error prevention, recognition rather than call flexibility and efficiency of use, aesthetic and minimalist design, and help and documentation. Data collection techniques used were questionnaires, observations and interviews sourced from the heuristic evaluation checklist given to 8 respondents. Evaluation results consist of improved feedback, error messages, help features, letter order, tasks and important items, handling the number of words in the data entry column.